To Determine the Role of Clonidine as an Adjuvant to Intrathecal Bupivacaine in Patients Undergoing Lower Abdominal Surgery - Priyanka Deshmukh1 , Pratibha Deshmukh2 , Sohal Parate3 , Aruna Chandak4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Clonidine is an alpha-2 adrenergic agonist with various actions, one of which enhances theeffectiveness of local anaesthetics. For patients undergoing lower abdominal surgery, we examined the effectof adding intrathecal clonidine to hyperbaric bupivacaine on postoperative pain relief and side effects, if any.Aim: To assess the efficacy of intrathecal clonidine along with hyperbaric Bupivacaine in patients undergoinglower abdominal surgeries.Method: It was a retrospective study carried out under spinal anaesthesia on 80 patients undergoing lowerabdominal surgery. The research population was assigned randomly to two groups; group B- received 15 mgbupivacaine+ 0.4mi Normal Saline and group C received 15 mg bupivacaine + 60mcg clonidine.Results: Addition of 60mcgs of intrathecal clonidine to 0.5% hyperbaric bupivacaine significantly prolongedthe duration of motor & sensory blockade along with the duration of effective postoperative analgesia. Thedemand for rescue analgesic was earlier in group B as compared to group C. Both groups were matched forthe side-effects like hypotension, bradycardia, nausea, vomiting, and shivering